2005
DOI: 10.1111/j.1467-8551.2005.00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Complexity Theory and Strategic Change: an Empirically Informed Critique*

Abstract: We present a four-year ethnographic study of a public-sector organization and use narrative to describe its development in terms of four complexity theory concepts: sensitivity to initial conditions, negative and positive feedback processes, disequilibrium and emergent order. Our study indicates that order emerges at the boundary between the organization's legitimate and shadow systems. We suggest that the underlying dynamic leading to the emergent order is the need to reduce anxiety. Our findings cause us to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 44 publications
1
78
0
4
Order By: Relevance
“…For example, one area where CAS theory has been strongly advocated, but where its plurality and lack of coherence has proved problematic, is in the study of social systems like organisations. Results of such studies have shown that during their development, organisations tend towards equilibrium and stability rather than novelty or dynamism and that power differentials and other psycho-sociological factors are more relevant than those relating to adaptive behaviour, self-organisation or emergence [15]. As social organisations, the food businesses that provide the case studies for this paper are used to illustrate that practically this "tendency towards equilibrium" can be overcome when an organisation needs to respond to complex and uncertain future environments or "turbulence."…”
Section: Theoretical Foundations and Methodsmentioning
confidence: 99%
“…For example, one area where CAS theory has been strongly advocated, but where its plurality and lack of coherence has proved problematic, is in the study of social systems like organisations. Results of such studies have shown that during their development, organisations tend towards equilibrium and stability rather than novelty or dynamism and that power differentials and other psycho-sociological factors are more relevant than those relating to adaptive behaviour, self-organisation or emergence [15]. As social organisations, the food businesses that provide the case studies for this paper are used to illustrate that practically this "tendency towards equilibrium" can be overcome when an organisation needs to respond to complex and uncertain future environments or "turbulence."…”
Section: Theoretical Foundations and Methodsmentioning
confidence: 99%
“…While constructive criticism is generally delivered with the intent of improved performance, such as in the context of feedback interventions, hostile criticism aimed at an outstanding leader is generally delivered with the intent to spur some kind of change due to current dissatisfaction. It may be that, similar to negative feedback models discussed by strategy theorists, hostile criticisms are delivered when there is a need to tighten the difference between desired and actual behavior (Houchin & MacLean, 2005). Thus, it is likely that hostile criticisms may significantly impact leader change behaviors.…”
Section: Criticism Frameworkmentioning
confidence: 99%
“…In the past decade, the complexity theory has been popular among researchers seeking to understand organisational change (Houchin & MacLean, 2005). Stemming from the chaos theory (Sammut-Bonnici & Wensley, 2002), the complexity theory suggests that the increasing complexity of all systems over time leads to more changes, and the cycle starts over again (Mason, 2007).…”
Section: The Emergent Approachmentioning
confidence: 99%